(untitled) (Al Insyirah International Scientific Conference on Health, 2023)
Hypertension and type 2 diabetes mellitus are long-term diseases that are major health problems around the world, especially in Indonesia. They can lead to complications and even death. To reduce complications and deaths from these two diseases, people need to take their medicines as prescribed. Medication adherence is how many of the drugs a doctor gives a patient that the patient takes regularly for a certain amount of time. The Indonesian government is setting up a Chronic Disease Management Program (Prolanis) and a Referral Back Program (PRB) run by the Health Social Security Administration (BPJS) to make it easier for Prolanis patients to get the drug. These programs are meant to lower the risk of complications for people with hypertension and type 2 diabetes mellitus. The goal of this study was to find out the adherence of medication from Prolanis patients in Pekanbaru. This study was a quantitative observational analysis with a cross-sectional analytical design and a cluster sampling sample of 108 people. A questionnaire was used to get the information. In this study, 77 respondents (71.3%) were obedient in taking medications, and 31 respondents (28.7%) were not obedience.